Phenotyping of autoreactive B cells with labeled nucleosomes in 56R transgenic mice. Issue 1 (December 2017) - Gies, Vincent; Bouis, Delphine; Martin, Mickaël; Pasquali, Jean-L.; Martin, Thierry; Korganow, Anne-S.; Soulas-Sprauel, Pauline
Abstract The phenotypic characterization of self-reactive B cells producing autoantibodies is one of the challenges to get further insight in the physiopathology of autoimmune diseases. We took advantage of our previously developed flow cytometry method, using labeled nucleosomes, prominent autoantigens in systemic lupus erythematosus, to analyze the phenotype of self-reactive B cells in the anti-DNA B6.56R mouse model. We showed that splenic anti-nucleosome B cells express mostly kappa light chains and harbor a marginal zone phenotype. Moreover, these autoreactive B cells fail to acquire a germinal center phenotype and are less abundant in the transitional T3 compartment. In conclusion, the direct detection of autoreactive B cells helped determine their phenotypic characteristics and provided a more direct insight into the B cell tolerance process in B6.56R mice. This method constitutes an interesting new tool to study the mechanisms of B cell tolerance breakdown in B6.56R mice crossed with autoimmune prone models.